2020
DOI: 10.1115/1.4047328
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Dual-Fuel Combustion by Different Port Injection Fuels (Neat Ethanol and E85) in a DE95 Diesel/Ethanol Blend Fueled Compression Ignition Engine

Abstract: This paper investigated the effect of different substitution ratios of neat ethanol (E100) and ethanol–gasoline blend E85 on in-cylinder combustion, engine efficiency, and exhaust emissions, in a dual-fuel diesel engine, using the ethanol–diesel blend (DE95). Experimental studies realized at 1400 rpm, 1600 rpm, and 1800 rpm engine speeds under constant engine load of 50% (20 Nm). For each engine speed, the injection timing of diesel and E95 fuels at 24 °CA bTDC kept constant while low-reactivity fuels (i.e., E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(10 citation statements)
references
References 53 publications
0
9
0
1
Order By: Relevance
“…Figs. 6 shows the comparison of the power generation efficiency of the thermoelectric generator using three different thermoelectric modules with and without the metal foam. As shown in the figure, the thermoelectric conversion efficiency increases with the use of the high-performance module and the enhancement of heat exchange.…”
Section: Comparison Of Power Generation Performance Of Different Thermoelectric Modulesmentioning
confidence: 99%
See 1 more Smart Citation
“…Figs. 6 shows the comparison of the power generation efficiency of the thermoelectric generator using three different thermoelectric modules with and without the metal foam. As shown in the figure, the thermoelectric conversion efficiency increases with the use of the high-performance module and the enhancement of heat exchange.…”
Section: Comparison Of Power Generation Performance Of Different Thermoelectric Modulesmentioning
confidence: 99%
“…About 30-40% of the fuel energy in vehicles with internal combustion engines (ICEs) is released into the atmosphere as waste heat energy [5] . Carbon dioxide (CO2), unburned hydrocarbons (UHC), carbon monoxide (CO), nitrogen oxides (NOx) and particulate matter (PM) emitted into the atmosphere by internal combustion engines will cause environmental and health hazards [6][7] [8] . The engine efficiency could be increased by approximately 4-5% by converting the exhaust waste heat energy of ICEs into useful energy with thermoelectric waste heat recovery systems.…”
Section: Introductionmentioning
confidence: 99%
“…The results reveal that, nano particle mixed blends of neem methyl ester and die thy ester enhances the performance characteristics and reduce harmful emissions. Gurbuj et al (2020) conducted a study on dual fuel combustion by different port injection fuels (neat ethanol and E85) in a DE95 diesel ethanol blend CI Engine. The results showed that, dual fuel combustion achieved low brake thermal efficiency and combustion efficiency compared to single diesel fuel combustion.…”
Section: Introductionmentioning
confidence: 99%
“…13 The use of alcohols such as methanol and ethanol as a secondary fuel to reduce nitrogen oxides ( NO x ) and particulate matter ( PM ) emissions of diesel engines is quite common. 13 Ethanol is the most commonly used alcohol in diesel engines, 1416 although a high-octane number. 17 They play an essential role in reducing the soot and other harmful diesel emissions due to the molecular structure of oxygen bonds.…”
Section: Introductionmentioning
confidence: 99%